Comparison of different media for bacteriocine typing of Proteus mirabilis. - George, R H (1975)
The effect of a variety of nutrient bases on the production of bacteriocines by 10 standard Cradock-Watson types of Proteus mirabilis has been investigated. Differences in yield of greater than 10,000 fold were observed. Maximum yields were obtained with proteose peptone no. 3 (Difco) and a medium containing this with oxgall (Difco) as an antiswarming agent was developed for routine typing.